Guava market in Aguascalientes: an analysis to reduce price volatility - Ramos-Sandoval, Ivonne N.; García Salazar, J. Alberto; Borja Bravo, Mercedes; Guajardo Hernández, Lenin G.; Almeraya Quintero, S. Xochilt; Arana Coronado, Óscar A. (Revista Mexicana de Ciencias Agrícolas, 2017)
Seasonality of Guava ( Psidium guajava L.) production in  the state of Aguascalientes causes price volatility. In the  months of higher production, from October to January,  guava prices are lower than the annual average and lead  to a decrease in the producers’ profit while prices above  the average price occur in the remaining months. With the  objective of analyzing how some supply control actions  could avoid price volatility, the income and profit of guava  producers in the average year 2012-2015 (base situation)  and under two scenarios were calculated: practices of  agronomic management of the culture (calmeo) and  storage. The results indicate that in the average year  2012-2015 the gain of the producers of Aguascalientes  was 180.3 million pesos. A decrease of 8.5% in production  from October to January and a 15% increase from February  to September, thanks to the “calmeo”, would increase  producers’ profits to 214.1 million pesos. The storage of  10% of production in the months of October to January  would increase the producers’ profit to 216.1 million pesos.  The two alternatives increase producer gain; however, the  strong investment required to achieve storage requires  the practice of calmeo to be recommended as the most  favorable measure of supply control to avoid price  volatility.
Keywords: “calmeo”, guava, prices, profit, supply, volatility